2018
DOI: 10.1016/j.jfma.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mutation in Egyptian children with steroid-resistant nephrotic syndrome

Abstract: Our study concludes that mutations of NPHS2 gene are common among Egyptian children with SRNS. We support a model where ethnicity plays an important role in specific NPHS2 mutations, since a novel mutation was found in one patient in this study. Future study on a large number of Egyptian patients with SRNS is warranted to identify the actual genetic contribution of this gene in the development of SRNS in our population, which might help in patients' prognosis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Moreover, our study results were interestingly in keeping with the national study done in the Pediatric Nephrology Clinic, Cairo University Children's Hospital and Genetics Department, National Research Centre (2017). They did not discover mutation of p.R229Q in exon 5 among Egyptian children (18) .…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, our study results were interestingly in keeping with the national study done in the Pediatric Nephrology Clinic, Cairo University Children's Hospital and Genetics Department, National Research Centre (2017). They did not discover mutation of p.R229Q in exon 5 among Egyptian children (18) .…”
Section: Discussionmentioning
confidence: 92%
“…Different genetic mutations in different populations make the need for genetic testing and histological pattern determination of different populations valuable for disease prognosis and management. There have been previous studies screening for NPHS2 mutations in the Egyptian population that showed novel mutations [51,52]. Therefore, in this study we looked for new mutations of the PLCE1 gene in Egyptian SRNS patients.…”
Section: Discussionmentioning
confidence: 99%
“…NPHS2 mutations first found in early-onset autosomal recessive familial and sporadic SRNS (44). NPHS2 gene harbors 8 exons and encodes podocin, an interrelated protein with nephrin.…”
Section: Podocinmentioning
confidence: 99%